Particular Defect Analysis of Semi-Finished Component (Lesser Size Defects) - Lenin Rakesh, N.; Durairaj, V.P.; Kumar Pandey, Nitesh; Singh, Karan; Sahid Akhtar, Md. (International Journal of Psychosocial Rehabilitation, 2019)
Rejection of finished or semi-finished products in any industry is always undesirable and intolerable. The study is carried out to examine the root causes of various defects and imperfections of products in industries that arise during different stages of manufacturing. After identification of flaws by experiments, research remedies are also determined to reduce the intensity and potential of their occurrence. In pursuance, a detailed study of the manufacturing process was performed. Bottlenecks and weak points of the systems have been noted. The success of the study not only enhanced productivity of the industry but also reduced the production cost of the final product by minimizing wastage in terms of rejection, thereby increasing the competitiveness